2022
DOI: 10.26418/jmars.v10i2.55797
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Kenyamanan Termal Ruang Pada Rumah Betang Ensaid Panjang Di Kabupaten Sintang

Abstract: Traditional architecture is an architectural form that passed down from one generation to the next. Traditional houses are formed through a long time that are responsive to the environment. The traditional houses adapt with the environment to increase their level of comfort and reduce disturbances for a comfortable living. This study aimed to identify the thermal comfort of Betang Ensaid Panjang, which is the traditional Dayak houses in Sintang Regency. Identification of the thermal comfort was done by measuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In Lamin's house, the roof serves as an element that dominates the house. The research found that the roof maximized heat transfer, as in the Brusu Dayak tribe living in North Kalimantan 22) and Betang Ensaid Panjang, the traditional Dayak house in Sintang Regency 23) . A research method includes direct surveys and measurements of several points in a traditional house, including measurements of temperature, humidity, and air movement 22,23) .…”
Section: Lamin House Passive Designmentioning
confidence: 94%
See 2 more Smart Citations
“…In Lamin's house, the roof serves as an element that dominates the house. The research found that the roof maximized heat transfer, as in the Brusu Dayak tribe living in North Kalimantan 22) and Betang Ensaid Panjang, the traditional Dayak house in Sintang Regency 23) . A research method includes direct surveys and measurements of several points in a traditional house, including measurements of temperature, humidity, and air movement 22,23) .…”
Section: Lamin House Passive Designmentioning
confidence: 94%
“…The thermal comfort of Lamin houses varies at different times in different spaces 22,23) . As a result, it can be classified as slightly cool in the morning, warm in the afternoon and evening, and comfortable at night.…”
Section: Lamin House Passive Designmentioning
confidence: 99%
See 1 more Smart Citation